Novel Indicators of Anthropogenic Influence on Marine and Coastal Ecosystems - Feist, Blake E.; Levin, Phillip S. (Frontiers in Marine Science, 2016)
Human populations are concentrated along coastal regions worldwide, placing a disproportionate stress on coastal marine ecosystems. Ironically, biogenic habitats may be adversely affected by human activities though they serve to attenuate the impacts of global change on coastal cities. Surprisingly, simple, coastwide indicators of anthropogenic influences in relation to the spatial distribution of biogenic habitats are relatively underdeveloped. In this paper, we introduce a spatially explicit index of coastal as well as upland riverine human population proximity, based on human population and river dynamics datasets on the West- and Gulf-Coasts of the US. We then examine the relationship between these indices and biogenic habitats (kelp and mangrove forests). Finally, we identify patterns of landscape-scale biodiversity with human populations, and explore occurrence of biogenic habitats within and outside of marine protected areas (MPAs). We found that biogenic habitats were negatively associated with human populations and that MPAs were generally placed away from people. Landscape-scale patterns of biodiversity did not differ within and outside kelp forests and MPAs on the West Coast, but had a negative association with mangroves and a positive association with MPAs on the Gulf Coast. This index can be used anywhere in the world, can project into the future using various human population growth forecasts, and can serve as an important method for conservation triage.